Is intralesional resection suitable for central grade 1 chondrosarcoma: A systematic review and updated meta-analysis. Issue 9 (September 2017) - Chen, X.; Yu, L.J.; Peng, H.M.; Jiang, C.; Ye, C.H.; Zhu, S.B.; Qian, W.W.
Abstract: Background: The surgical choice for grade 1 chondrosarcoma has been debated for decades. Intralesional resection can minimize the damage caused by surgery and offer better functional outcome. However, controversy remains about whether it will result in higher rates of local recurrence and metastasis, fewer complications, and better functional outcome compared with resection with wide margin. This systematic review and updated meta-analysis therefore compared intralesional resection and resection with wide margin in terms of local recurrence, metastasis, complications, and functional outcome. Methods: Medline, Embase, and the Cochrane Library were comprehensively searched in December 2016 to identify studies comparing intralesional resection and resection with wide margin for central grade 1 chondrosarcoma. Data of interest were extracted and analyzed using Review Manager 5.3. Results: Ten studies involving 394 patients were included, with 214 patients who had intralesional resection and 180 patients who had resection with wide margin for grade 1 chondrosarcoma. Intralesional resection was associated with lower complication rates (P < 0.0001) and better Musculoskeletal Tumor Society score (MSTS). There were no significant differences in terms of overall local recurrence (P = 0.27), local recurrence based on adjuvant therapies (P = 0.22), local recurrence in studies that included lesions of the hand, foot, pelvis, and axial skeleton (P = 0.55), and metastasis (P = 0.74) between groups. Conclusion: Intralesional resection provides lower complications and better functional outcome with no significant increase in the risk of recurrence and metastasis. We think it is a suitable treatment for central grade 1 chondrosarcoma.